Contemporary morphological theories : a user's guide - Stewart, Thomas W., 1967- (Edinburgh University Press, 2016)
Provides a valuable guide to existing approaches in morphological analysis. Analyzing three descriptive challenges for morphology (Scottish Gaelic nouns, Georgian verbs, and Sanskrit compound verbs), and comparing and contrasting the backgrounds and fundamentals of leading approaches to word structure and lexical relationships, this book explores the way each framework proceeds from its author's basic assumptions, revealing how they can either complement or compete with other approaches.